Transformasi Kepemimpinan Organisasi Belajar Mahasiswa melalui Kunjungan TPST Bantar Gebang - Indica Yona Okyranida; Sari Prabandari; Cicilia Emita; Robinson Situmorang; Muhammad Japar (Universitas Indraprasta PGRI, 2025)
Leadership transformation among Science, Technology, Engineering, and Mathematics (STEM) academics is crucial for addressing modern systemic challenges, such as the environmental crisis. A learning approach capable of integrating theoretical knowledge with socio environmental realities is required. This study aims to analyze the extent to which a field visit to the Bantar Gebang Integrated Waste Management Site (TPST) encouraged the leadership transformation of 65 physics students, measured through Peter Senge's Five Disciplines of the Learning Organization framework. The research adopts a descriptive qualitative approach with a single case study design. Data collection, following Kolb’s Experiential Learning Cycle (ELC) model (with the visit serving as the Concrete Experience), was conducted in two phases. The first phase involved collecting Structured Reflection Questionnaires (qualitative narratives from N=65) to measure Personal Mastery and Mental Models. The second phase included in-depth interviews (key informants) and document analysis (work programs, minutes) to explore shared vision, team learning, and systems thinking. All data were analyzed using thematic analysis. The visit served as a concrete experience triggering significant paradigm shifts, particularly in the reinforcement of systems thinking Senge's key discipline.